University of Pennsylvania Radiocarbon Dates IV - Ralph, Elizabeth K.; Ackerman, Robert E. (Radiocarbon, 1961)
With one exception, the radiocarbon dates in this list were reported previously by Rainey and Ralph (1959). For discussions of the reliability of the dates, of the materials dated, and of the correspondence of the dates with estimated arctic chronologies, the reader is urged to refer to the original publication. The radiocarbon determinations were made over a period of several years. Those processed before 1956 were dated by the solid-carbon method and are so labeled; others, by the carbon-dioxide method. The age calculations are based on the average of several samples dated archaeologically and by tree-rings, corrected to zero age (Rainey and Ralph, 1959, p. 365). By this means the errors due to atmospheric depletion (Suess effect) and to past changes in radiocarbon concentration (de Vries, 1958; Willis, Tauber, and Münnich, 1960) have been minimized. The b.p. dates are calculated from A.D. 1957 (solid-carbon) and A.D. 1958 (carbon dioxide).